Microalgae-based wastewater treatment for nutrients recovery: A review - Li, Kun; Liu, Qiang; Fang, Fan; Luo, Ruihuan; Lu, Qian; Zhou, Wenguang; Huo, Shuhao; Cheng, Pengfei; Liu, Junzhi; Addy, Min; Chen, Paul; Chen, Dongjie; et al. (Bioresource technology, 2019)
•Microalgae-based wastewater treatment conforms the new trends of wastewater treatment in future.•Most wastewater with inappropriate C/N and N/P ratios for microalgae cultivation.•Factors affecting nutrients recovery by microalgae are strongly related to the wastewater characteristics.•More research is needed on the design and operation of microalgae-based wastewater treatment process to be more economical. The water resource crisis and concerns with environmental pollution are pushing for upgrading of conventional wastewater treatment process. Microalgae-based wastewater treatment process has shown many advantages that can meet the new demand for improved wastewater treatment. However, considering the issues related to the complexity of wastewater characteristics and adaptability of microalgae species, and the challenges to the design and optimization of treatment processes in order to achieve higher removal efficiencies with lower costs, further exploration and research are still needed. This review provides an overview of microalgae strains commonly used for wastewater treatment, physical and chemical properties of various wastewaters and their suitability for algae cultivation, factors affecting algae growth, nutrient assimilation/removal and biomass productivity. The design and operation of microalgae-based wastewater treatment processes are also discussed. Moreover, the issues and limitations of microalgae-based wastewater treatment are also discussed and suggestions are proposed for the further research and development.